Under my bed - Dickson, John (Berbay Publishing Pty Ltd, 2018)
It's bedtime when monsters come out in search of food. With all that noise and those strange smells, sleeping is out of the question. So how can the monsters be stopped from ruining a good night's sleep when it's annual Monster Day and they just want to celebrate? Maybe it's time to join them!